STRAIN ELASTOGRAPHY EFFICIENCY FOR THYROID GLAND CANCER DIAGNOSIS - A. N. Katrich; A. V. Okhotina; A. A. Kvasova; N. S. Ryabin (Инновационная медицина Кубани)
Present study is based on diagnosis results of 61 patients with focal lesions in thyroid gland. In our paper we applied ultrasonic scanner Toshiba Aplio 500 with strain elastography function. All patients were indicated fine-needle aspiration biopsy and cytological examination of biopsy specimen. All patients were divided into two groups. The first group contained 19 patients with thyroid gland cancer, in the second group there were 42 patients with colloid cellular goiter. To assess results of strain elastography we applied scale Ueno with modification С. Asteria. After processing received results we had following data: focal lesions, valued in 3 and 4 points, were qualified properly in 15 patients, foci with 1 and 2 points were correct in 37 patients. Diagnostic efficiency for thyroid gland cancer diagnosis was: sensitivity – 78.9%, specificity – 88.1%, accuracy – 85.2%.